Comparative study of the tracheolar system in the cerebroid ganglion of Díptera. Hymenoptera and Lepidoptera: Sphingidae - PESSACQ, TOMÁS P. (Revista Colombiana de Entomología, 2000)
A comparative histologic study of the tracheal system in the nervous system of Diptera, Hymenoptera, and Sphingidae is made, by the employ of silver impregnation methods. The main structural and architectural characteristics of the cerebral ganglion are described.